Flow visualization of unsteady flow field around a monofin using PIV - Matsuuchi, K.; Hashizume, T.; Nakazawa, Y.; Nomura, T.; Shintani, H.; Miwa, T. (Biomechanics and Medicine in Swimming X, 2006)
Swimmers swimming with monofins are much faster than without although the human power is the same. To predict how fast they can swim we have to know the complex flow field which is extremely unsteady. The study of the flow field was executed in a flume using a kind of swim manipulator equipped with a monofin. We set the fin in a flume and drove it by a motor. Flow fields around a monofin in a pitching motion was measured by means of a recently-developed technique called the Particle Image Velocimetry (PPV). Time variations of velocity and vorticity fields were calculated from the image captured by PIV System. Unsteady flow characteristics such as a vortex formation and the movement of vortices were investigated in detail. Information on unsteady flow and vortex motion serves the understanding the mechanism of propulsion in aquatic motion.